Attenuation of Hepatic Graft-versus-host Disease in Allogeneic Recipients of MyD88-deficient Donor Bone Marrow - Lim, Ji-Young (Immune Netw, 2015)
Acute graft-versus-host-disease (GVHD) is characterized by selective damage to the liver, the skin, and the gastrointestinal tract. Following allogeneic hematopoietic stem cell transplantation, donor bone marrow (BM) cells repopulate the immune system of the recipient. We previously demonstrated that the acute intestinal GVHD (iGVHD) mortality rate was higher in MyD88-deficient BM recipients than that in the control BM recipients. In the present study, the role of MyD88 (expressed by donor BM) in the pathophysiology of hepatic GVHD (hGVHD) was examined. Unlike iGVHD, transplantation with MyD88-deficient T-cell depleted (TCD) BM attenuated hGVHD severity and was associated with low infiltration of T cells into the liver of the recipients. Moreover, GVHD hosts, transplanted with MyD88-deficient TCD BM, exhibited markedly reduced expansion of CD11b(+)Gr-1(+) myeloid-derived suppressor cells (MDSC) in the liver. Adoptive injection of the MDSC from wild type mice, but not MyD88-deficient mice, enhanced hepatic T cell infiltration in the MyD88-deficient TCD BM recipients. Pre-treatment of BM donors with LPS increased MDSC levels in the liver of allogeneic wild type BM recipients. In conclusion, hGVHD and iGVHD may occur through various mechanisms based on the presence of MyD88 in the non-T cell compartment of the allograft.